Conference spotlight: 21st Annual Meeting of the Swiss Stroke Society, the 1st Symposium of the Swiss Stroke Nursing Network and the Swiss Stroke Trialists' Meeting. Issue 1 (30th January 2019) - Michel, Patrik; Mösinger, Doris; Hirt, Lorenz; Arnold, Marcel
The 21st Annual Meeting of the Swiss Stroke Society held in Lausanne, Switzerland, from the 11th to 12th January 2018 at Lausanne University Hospital (CHUV) included scientific sessions about vasculitis, hyperacute stroke management, the old and polymorbid stroke patient, and cerebral aneurysms/vasospasms and inaugurated the 1st Symposium of the Swiss Stroke Nursing Network.